Ngā tūpuna o Te Whanganui-a-Tara. - Clarke, Sandra, 1941- (Wellington City Council & Wellington Tenths Trust, 2005)
Short biographies and some portraits of Māori associated with the Te Āti Awa community at Port Nicholson (Te Whanganui-a-Tara) in the 1830s.